The best technology writing 2010 - Dibbell, Julian (Best Technology Writing., 2010)
The iPad. The Kindle. Twitter. When the Best Technology Writing series was inaugurated in 2005, these technologies did not exist. Now they define our 21st-century lives. As Julian Dibbell writes in his introduction to The Best Technology Writing 2010, "The digital is us. Yet for that reason, it is also something more, a lightning rod for our feelings about technology in general." Whether it is Sam Anderson's giddy but troubled defense of online distractions, David Carr's full-throated elegy to the dying world of pre-digital publishing, Steven Johnson's warm appreciation of Twitter's bite-size contributions to collective human intelligence, or Evan Ratliff's fascinating month-long quest to disappear without a digital trace, many of the essays gathered here register our intense and complicated fascination with digital media. But as Dibbell notes, these essays also remind us that some of the most disruptive and fascinating technologies continue to come from beyond the digital world. Jill Lepore's writing on the politics of breast-feeding gadgetry, Stephen Silberman's investigation of the placebo effect in pharmaceutical testing, Burkhard Bilger reporting on efforts to build a better cook stove for the developing world, and Tad Friend's profile of electric-car developer Elon Musk's efforts to head off environmental catastrophe all invite us to reflect on how many aspects of human experience remain fundamentally unchanged by digital technology. Packed with marvelous essays on technologies old and new, The Best Technology Writing 2010 is an outstanding addition to this "fantastic" (Cory Doctorow), "fascinating" (Chris Anderson) series. The Best Technology Writing 2010 includes essays written by:Sam AndersonBurkhard BilgerJoshua BearmanMark BowdenDavid CarrDouglas FoxTad FriendBen GreenmanVanessa GrigoriadisJames HarkinAdam HigginbothamAlex HutchinsonSteven JohnsonKevin KellyJill LeporeAlexis MadrigalJavier MariasMike MassiminoEvan RatliffDaniel RothClay ShirkySteve SilbermanAnnie TrubekLawrence Weschler.